The genus Orobothriurus Maury in central Argentina with description of a new species from El Nevado mountain chain in Mendoza Province (Scorpiones: Bothriuridae) - Ojanguren-Affilastro, Andrés Alejandro; Campón, Florencia Fernández; Silnik, Susana Lagos; Mattoni, Camilo Iván (Zootaxa, 2009)
New data on the scorpion genus Orobothriurus Maury 1976 in central Argentina are provided. Orobothriurus grismadoi n. sp. is described; this species occurs in high altitudes in El Nevado mountain chain, an isolated orographic system in Southern Mendoza, Argentina, separated by almost 200 km from the Andes Mountain chain. This species is closely related to Orobothriurus alticola (Pocock, 1899). This is the southernmost record for the genus about 300 km south from previous records. Orobothriurus bivittatus (Thorell, 1877) is synonymised with O. alticola based on material recently collected in El Tontal mountain chain. We also provide new data about the distribution and intraspecific variability of O. alticola.